Movimientos sociales en la era de las redes sociales - Peña, Daria (2021)
It is clear that social movements are not the same since the emergence of social networks. They have definitely revolutionised the way we express ourselves, communicate and organise. However, they are a double-edged tool. In this essay I analyse the main characteristics of social movements in the network era, mainly from two perspectives: that of Manuel Castells and that of Byung-Chul Han. Thus, I will determine whether they are experiencing a favourable or detrimental development with respect to the achievement of their objectives and, above all, I will make visible the new obstacles that appear in virtuality in order to overcome them.